STRATEGI REKRUTMEN TERHADAP SUMBER DAYA INSANI - Holisatul Munawaroh; Amir; Ahmad Hamdi (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
Employee recruitment is carried out with the main goal of a company or organization being to find and determine employees who match the company's criteria so that later they are able to make changes to the company because quality employees will certainly increase the company's quality as well. And every company has a different way of recruiting employees. The results of this study indicate that CV. AL Mubarakah combines external and internal sources in recruiting employees. The method used is a closed method and various recruitment processes carried out by CV. Al Mubarakah is starting from the preparation of a recruiting strategy, searching for job applicants, making a pool of applicants, and interviews to select prospective new employees. Supporting factors in the recruitment are easier search for applicants, vacant vacancies are filled faster, employees work more flexibly and relaxed. The inhibiting factors for recruitment are the closed implementation method, it is more difficult to get qualified employees, compensation policies and external environmental conditions.